Interactions between the effects of food and water motivating operations on food‐ and water‐reinforced responding in mice. Issue 3 (30th April 2019) - Lewon, Matthew; Spurlock, Emily D.; Peters, Christina M.; Hayes, Linda J.
Abstract : Two experiments examined interactions between the effects of food and water motivating operations (MOs) on the food‐ and water‐reinforced operant behavior of mice. In Experiment 1, mice responded for sucrose pellets and then water reinforcement under four different MOs: food deprivation, water deprivation, concurrent food and water deprivation, and no deprivation. The most responding for pellets occurred under food deprivation and the most responding for water occurred under water deprivation. Concurrent food and water deprivation decreased responding for both reinforcers. Nevertheless, water deprivation alone increased pellet‐reinforced responding and food deprivation alone likewise increased water‐reinforced responding relative to no deprivation. Experiment 2 demonstrated that presession food during concurrent food and water deprivation increased in‐session responding for water relative to sessions where no presession food was provided. Conversely, presession water during concurrent food and water deprivation did not increase in‐session responding for pellets. These results suggest that a) the reinforcing value of a single stimulus can be affected by multiple MOs, b) a single MO can affect the reinforcing value of multiple stimuli, and c) reinforcing events can also function as MOs. We consider implications for theory and practice and suggest strategies for further basic research on MOs.